2003
DOI: 10.3168/jds.s0022-0302(03)73995-2
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the Interfacial Behavior of β-Casein on Phosphoserine Residues

Abstract: The role of the phosphoserine residues on the dynamical and structural properties of beta-casein was studied by molecular dynamics of the protein in water/lipid interfacial regions. The initial protein structure adopted in the modeling was that proposed for bovine beta-casein A2, where the five phosphoserine residues, originally present in its primary structure, were partially or totally substituted by serine residues. The simulations revealed a dependence of the interfacial behavior of beta-casein on the phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Molecular modelling clearly indicated the protein affinity for the interface, with the macromolecular dipole defining the protein orientation relative to the interface, eventually leading to a less extended conformation in a dielectrically discontinuous environment. [6][7][8] These studies also confirmed the role of the phosphate group in the -casein molecule with respect to its interfacial properties, as demonstrated experimentally. It has been reported that removal of the phosphate groups from whole casein reduces its ability to maintain emulsion integrity.…”
Section: Introductionsupporting
confidence: 72%
“…Molecular modelling clearly indicated the protein affinity for the interface, with the macromolecular dipole defining the protein orientation relative to the interface, eventually leading to a less extended conformation in a dielectrically discontinuous environment. [6][7][8] These studies also confirmed the role of the phosphate group in the -casein molecule with respect to its interfacial properties, as demonstrated experimentally. It has been reported that removal of the phosphate groups from whole casein reduces its ability to maintain emulsion integrity.…”
Section: Introductionsupporting
confidence: 72%
“…Lorenzen and Reimerdes (1992) showed that dephosphorylation of α s -and β-casein stabilized the creaming behavior of oil/water emulsions. By molecular dynamics, Cassiano and Area (2003) reported that the affinity of totally dephosphorylated β-casein for water/lipid interface was lower than β-casein which was able to be inserted in the water/lipid interface.…”
Section: Dephosphorylationmentioning
confidence: 99%
“…In solution, phosphoserine chelates calcium and binds directly to crystal faces to interrupt crystal growth [37,47]. When phosphoserine is bound, embedded as matrix components (i.e., phosphatidyl-serine [46,49], or within proteins in saliva (i.e., statherin [50,51]) or dairy products (i.e., casein [52,53])), it can prevent mineralization in supersaturated fluids by chelating calcium, stabilizing amorphous calcium phosphate complexes, and direct binding to crystal surfaces. Alternatively, bound phosphoserine can facilitate mineralization by increasing the local concentration of sequestered ions, and ionic bonding [54,55].…”
Section: Introductionmentioning
confidence: 99%